Online Teaching: Creating Text-Based Environments for Collaborative Thinking - Lapadat, Judith C. (Alberta Journal of Educational Research, 2004)
This article examines some of the ways graduate students engage in interactive writing in online university courses as a means of discussion. In particular I present data from course transcripts that suggest that discursive interaction in an asynchronous, text-based, online course may be uniquely suited to fostering higher-order thinking and social construction of meaning. I support this argument by considering the emergent online community and its participation structures, qualities of the interactive written discourse, and means by which the discourse supports making meaning and higher-order thinking. Findings support research that suggests that well-designed, text-based, online courses for university students create collaborative learning environments that enhance thinking.